PENOLAKAN PETER PAN UNTUK MENJADI DEWASA DALAM NOVEL PETER AND WENDY KARYA J.M BARRIE - KUMOLONTANG, ELISABETH PRISKILA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTÂ This research is entitled â€œPenolakan Peter Pan untuk menjadi dewasa dalam novel Peter and Wendy karya J.M Barrieâ€ is written to fullfil the requirement of accomplishing bachelorâ€™s degree in English Department Faculty of Humanities Sam Ratulangi university. The focus of this research is Peter Panâ€™s rejection in the novel.The writer use theory from Leary (2001) to analyze rejection in the novel. This research alsoÂ  include reason and impact of the rejection. The writer use extrinsic approach to discuss about relation of psychology and literary to identify, analyze, and describe about Peter Panâ€™s rejection who portrayed in the novel Peter and Wendy and to analyze the impact of Peter Panâ€™s rejection.The result of this research is Peter Panâ€™s rejection for being mature is also relate to his past, before he live with the fairies. Peter Panâ€™s rejection about maturation in this is portrayed with the other character. From the rejection for being mature, the writer find six impact from the rejection.Keywords: Character, Rejection, Peter Panâ€™s Rejection